Recent Structure Development of Poly(vinylidene fluoride)-Based Piezoelectric Nanogenerator for Self-Powered Sensor - Cheoljae Lee; Hyosik Park; Ju-Hyuck Lee (Actuators, 2020)
As the internet of things (IoT) era approaches, various sensors, and wireless electronic devices such as smartphones, smart watches, and earphones are emerging. As the types and functions of electronics are diversified, the energy consumption of electronics increases, which causes battery charging and maintenance issues. The piezoelectric nanogenerator (PENG) received great attention as an alternative to solving the energy issues of future small electronics. In particular, polyvinylidene fluoride (PVDF) piezoelectric polymer-based PENGs are strong potential candidate with robust mechanical properties and a high piezoelectric coefficient. In this review, we summarize the recent significant advances of the development of PVDF-based PENGs for self-powered energy-harvesting systems. We discuss the piezoelectric properties of the various structures of PVDF-based PENGs such as thin film, microstructure, nanostructure, and nanocomposite.